Cyperus kilelai (Cyperaceae), a new species from a thermal spring in Katanga (Democratic Republic of the Congo) - Attila Mesterházy; Marc Reynders; Mylor Ngoy Shutcha (Plant Ecology and Evolution, 2024)
Background – During field work performed in 2018 by the University of Lubumbashi in the Katanga region of D.R. Congo, a peculiar Cyperus species was discovered at the edges of a thermal spring in the southwest corner of the Upemba graben, near the city of Luena. Material and methods – Herbarium material from the collected plant was studied and used as a basis for illustrations and a SEM study of the nutlets. A preliminary IUCN Red List assessment was performed according to the IUCN Guidelines and Criteria. Results – Cyperus kilelai, a new species from Katanga in D.R. Congo, is described and illustrated. This small tussocky species is characterised by weakly 3–4 angled dimerous nutlets with stigma branches in ad- and abaxial positions and glumes of 2.5–3.2 mm long. It is currently only known from its type location. Thermal springs in this region are of interest for the development of geothermal power plants in the near future. Based on the restricted area, a small population size, and a plausible future threat, the conservation status of this species is preliminarily assessed as Vulnerable.